The inventory of the books of the abbey library of Cistercians in Szczyrzyc until the end of nineteenth century - Marszalska, Jolanta M. (Saeculum Christianum. Pismo Historyczne, 2021)
The first historically confirmed records of the library of Szczyrzyc monastery are from the time of abbot Joahim I Cieniawski (1592-1607). Among the 40 titles of books recorded during the visitation in 1597 was: six antiphonals, eight missals, five psalters, four graduals, two copies of the Bible, homiliarz, kolektarz, the life of St. Stanislaus bishop and martyr, the St. Benedict’s rule and also Liber Definitorum, which is the book of the resolution of the General Chapters of the Cistercian. The first catalogue of books was made in 1755 and was entitled Cathalogus librorum Monasterij Ciricensis iuxta alphabetum authorum mense Augusto Anno Domini 1755. Conscriptus. It is a pity that only two initials cards including a list of books within the letter “A” were preserved until modern times. Three nineteenth century inventories provide full knowledge about this collection of books taking into account the title of a book, the author’s name, the description of a book (place and year of publication) and format of a book. The person who wrote the book made their thematic segregation. Undoubtedly the number of books, titles and in particular the authors demonstrate the need and the importance which the Szczyrzyc monastery given to the books which reading had to help the monk in his pilgrimage to God.